The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1529/biophysj.108.132217
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Modulus Directs Neural Stem Cell Behavior

Abstract: Although biochemical signals that modulate stem cell self-renewal and differentiation were extensively studied, only recently were the mechanical properties of a stem cell's microenvironment shown to regulate its behavior. It would be desirable to have independent control over biochemical and mechanical cues, to analyze their relative and combined effects on stem-cell function. We developed a synthetic, interfacial hydrogel culture system, termed variable moduli interpenetrating polymer networks (vmIPNs), to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

53
878
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 952 publications
(946 citation statements)
references
References 49 publications
53
878
3
1
Order By: Relevance
“…Mammalian cells are commonly attached to their surrounding cells or extracellular matrix, which are associated with young's modulus in the range of 10 Pa-10 kPa (Yeung et al 2005;Saha et al 2008). Therefore to assess cellular responses, previous studies have used different elastic moduli of substrates (for instance, 42 Pa-280 kPa (Stroka & Aranda-Espinoza 2011a) and 10 Pa-10 kPa (Saha et al 2008)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian cells are commonly attached to their surrounding cells or extracellular matrix, which are associated with young's modulus in the range of 10 Pa-10 kPa (Yeung et al 2005;Saha et al 2008). Therefore to assess cellular responses, previous studies have used different elastic moduli of substrates (for instance, 42 Pa-280 kPa (Stroka & Aranda-Espinoza 2011a) and 10 Pa-10 kPa (Saha et al 2008)).…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have confirmed the importance of surface chemistry in cell-substrate interaction for successful performance of implants or tissue engineered constructs, the impact of mechanical parameters of substrate, such as stiffness on cellular functions has only been studied in the past 10 years Yeung et al 2005;Saha et al 2008;Byfield et al 2009;Stroka & Aranda-Espinoza 2011a;Yeh et al 2012;Huang et al 2013;Ataollahi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additional related studies have emphasized the critical role of hydrogel stiffness in skeletal muscle stem cell self-renewal 12 , neural stem cell behavior 13 and megakaryocyte poiesis 14 . 3D mechanical properties are similarly important in controlling adult stem cell fate in alginate hydrogels incorporating adhesive ligands 4 .…”
Section: Static Hydrogels That Mimic Biophysical Cuesmentioning
confidence: 99%
“…In the last decade, matrix stiffness alone has been implicated in regulating cellular functions, such as contraction 3,4 , migration 5,6 , proliferation 7,8 and differentiation 9,10 . With this in mind, a variety of natural (for example, gelatin, collagen) and synthetic (for example, polyacrylamide) polymer systems were used in vitro to mimic the elasticity of native tissues, which varies significantly throughout the body (for example, brain: ~0.2-1 kPa (refs [11][12][13], muscle: ~10 kPa (ref. 10), osteoid: ~30-45 kPa (ref.…”
mentioning
confidence: 99%